Sistema para controle de eventos da UTFPR - Menezes, Isabella de Araujo Cionini (2014)
The use of a system for the control of everyday activities has the function to automate tasks, making them easier and faster, it also allows you to reduce the number of errors during the tasks. The improvement is due to the fact that systems can offer controls that help verify and monitor quality aspects. Aiming to assist both in the management and in the conduct of the activities involved in the preparation and implementation of events, as result of this work a system was implemented to control the events of the Federal Technological University of Paraná, Campus Pato Branco. This system will allow controlling the processes that are involved in holding an event at the University, from its conception to its realization, being also possible to register a feedback through the same event report. To model and implement a system, there are several techniques of analysis and design. The chosen analysis technique was the Object orientation, and the Java programming language for web to implement the system, because of the easiness offered by the object orientation's concepts and technologies, associated to the development of web applications.